2016
DOI: 10.1038/srep38308
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal stem cells program macrophage plasticity by altering their metabolic status via a PGE2-dependent mechanism

Abstract: Mesenchymal stem cells (MSCs) are speculated to act at macrophage-injury interfaces to mediate efficient repair. To explore this facet in-depth this study evaluates the influence of MSCs on human macrophages existing in distinct functional states. MSCs promoted macrophage differentiation, enhanced respiratory burst and potentiated microbicidal responses in naïve macrophages (Mφ). Functional attenuation of inflammatory M1 macrophages was associated with a concomitant shift towards alternatively activated M2 sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
283
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(312 citation statements)
references
References 58 publications
14
283
2
3
Order By: Relevance
“…Interestingly, recent investigations have shown that human MSCs could alter macrophage phenotype by producing PGE2 in vitro 40, 52 . Additional experiments related to other MSC-secreted factors such as PGE2 are required to determine their effects on macrophages in IBD models.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent investigations have shown that human MSCs could alter macrophage phenotype by producing PGE2 in vitro 40, 52 . Additional experiments related to other MSC-secreted factors such as PGE2 are required to determine their effects on macrophages in IBD models.…”
Section: Discussionmentioning
confidence: 99%
“…The force on the cells was adjusted by adjusting the weight of the glass beads in the cups. After 12 hr of 1 g/cm 2 force loading, the cells were co‐cultured with macrophages in 6‐well culture plates (Corning) as described previously (Vasandan et al, ). A total of 3 × 10 5 macrophages were seeded on a 6‐well plate, and 2 × 10 5 hPDLCs were seeded in a transwell chamber (0.4 microns, Millipore) and co‐cultured for 48 hr.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that MSC have the ability to directly influence the immunological properties of macrophages and neutrophils by secreting factors such as PGE 2 , IL‐6, IL‐8, or IFN‐β . Following exposure to MSC‐secreted factors, macrophages develop increased phagocytosis, mediated in part by NADPH oxidase activation .…”
Section: Introductionmentioning
confidence: 99%